Effect of post coating processing on the morphological and mechanical properties of plasma Spray-reinforced hydroxyapatite coating. (2022) - Singh, Gursharan; Mittal, Manoj; Singh, Jujhar; Sharma, Shubham; Singh Chohan, Jasgurpreet; Kumar, Raman
Abstract: The biocompatible Hydroxyapatite (H.A.) coating helps titanium alloy recover and insulates implants from the body's environment. FDA recommends plasma spray to cover H.A. on body implants. H.A.'s poor mechanical properties limit its use in weight-bearing orthopaedic applications like hip and knee joints. This study examines the influence of H.A. reinforcement on plasma-sprayed coatings' microstructure and mechanical characteristics. The influence of thermal post-treatments on as-deposited (pure H.A. & reinforced H.A.) coatings was also examined. SEM images of as-deposited (pure H.A. & reinforced H.A.) coatings were taken before and after thermal processing (S.E.M.). The use of reinforcement improves as-sprayed coatings' microhardness and bond strength. After two hours at 700 °C in air, both substrates had ultrafine particles that may connect to bone and promote bone development.